On a General Class of Multiple Eulerian Integrals with Multivariable Gimel-Function (Global Journal of Science Frontier Research, 2018)
Recently, Raina and Srivastava [11] and Srivastava and Hussain [16] have provided closed-form expressions for a number of Motivated by these recent works, we aim at involving the product of multivariable I multivariable polynomials, a generalization of the Mittag function.
Keywords: multivariable gimel-function; multiple eulerian integral; multivariable polynomials; generalization